2014
DOI: 10.4100/jhse.2014.91.12
|View full text |Cite
|
Sign up to set email alerts
|

Design and validation of an observational instrument to assess the technical execution in top-rope climbing

Abstract: Hernández-Hernández, E., Caballero-Blanco, P., Gómez-Rodríguez, A., & Morenas-Martín, J. (2014). Design and validation of an observational instrument to assess the technical execution in top-rope climbing. J. Hum. Sport Exerc., 9(1), pp.111-123. The aim of this study was to design and validate an observational instrument to assess the technical execution in top-rope climbing. This observational instrument allows researchers to assess the progression of climbers in relation to the achievement of key aspects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 26 publications
0
8
0
1
Order By: Relevance
“…To our better understanding, we acknowledge that there are different types of instrument validation, like content validity, face validity, construct validity, and so forth [42]. Validity is explained by [29] as the degree or the extent to which a test measures what is presumed to measure. In this study, content validity was tested through the agreement and consensus means among seven expert judges.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To our better understanding, we acknowledge that there are different types of instrument validation, like content validity, face validity, construct validity, and so forth [42]. Validity is explained by [29] as the degree or the extent to which a test measures what is presumed to measure. In this study, content validity was tested through the agreement and consensus means among seven expert judges.…”
Section: Methodsmentioning
confidence: 99%
“…Technical execution focuses on the extremities of the body's limbs, including the arms and legs, using the key aspects of the movement with stages during the climb [28]. Recently a similar study was conducted on the form of instruments assessing the technical execution with top-roping [29]. Results showed that instruments designed present optimal levels of reliability and validity even though some experts suggested removing three aspects of them, namely the displacement of the hips, interaction segments between hands and feet, and the crossed force application.…”
Section: Introductionmentioning
confidence: 99%
“…These features should be part of the attitude measurement process. "Attitudes are not susceptible to direct observation but must be inferred from verbal expressions or observed behavior" [16]. "This indirect measurement is carried out using some scales starting from a series of affirmations, propositions, or judgments on which individuals express their opinion; based on this information, we deduce or infer attitudes" [17].…”
Section: Literature Reviewmentioning
confidence: 99%
“…With this validation, we attempted to create an instrument that is valid, reliable, functional, effective, and understandable. The validation of data collection instruments, their importance, and necessity has been the object of study of many investigations [24][25][26].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Segons la investigació duta a terme per Aguilera et al (2013), aquesta disciplina esportiva s'assembla a esports com el voleibol, el bàdminton o el tennis de taula on és possible trobar similituds en l'estructura temporal o també per la successió d'intervals d'acció i pausa (Palao, Santos, & Ureña, 2004;Pradas et al, 2010).També, entre voleibol i kinbol hi ha diverses similituds molt particulars d'aquest tipus d'esports, on qualsevol jugada o acció acaba amb la consecució per part d'algun dels equips participants d'un punt, sigui per encert o fallada de l'equip contrari o l'alta concentració de jugadors dins un mateix espai de joc, la qual cosa obliga a tenir una correcta coordinació per part dels participants perquè les funcions del joc s'executin adequadament (García-Tormo, Redondo, Valladares, & Morante, 2006;Hernández-Hernández & Palao, 2013). En definitiva, l'objectiu últim d'aquests dos esports és el mateix, evitar la caiguda de la pilota en la nostra possessió i enviar-la a l'equip contrari amb les màximes dificultats possibles per a la seva recepció.…”
unclassified